1996
DOI: 10.1088/0953-8984/8/22/012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of uniaxial pressure on the ferroelectric phase transition of TGSe crystals

Abstract: Isobaric studies of the influence of uniaxial pressure on the transitions of pure TGSe crystals for the three directions x, y, z (a * , b, c) are reported. The critical exponents, β, δ and γ , from dielectric constant and hysteresis loop measurements, as well as the coefficients ξ and ζ of the fourth and sixth powers of P in the free-energy expansion under uniaxial pressure were determined. It has been found that uniaxial pressure applied along the a * -axis keeps the transition near a tricritical point for 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
5
18
0
Order By: Relevance
“…Thus, under hydrostatic pressure of 1.5 GPa, ΔT c should amount to 30 K. Following other authors [21], it can be speculated that the effect of uniaxial pressure is equivalent approximately to that of a tenth of the hydrostatic pressure and ΔT c~+ 3 K can be expected due to the powder pressing, which is of the order of magnitude of the value found experimentally (Fig. 4).…”
Section: Comparison With Theoriessupporting
confidence: 72%
“…Thus, under hydrostatic pressure of 1.5 GPa, ΔT c should amount to 30 K. Following other authors [21], it can be speculated that the effect of uniaxial pressure is equivalent approximately to that of a tenth of the hydrostatic pressure and ΔT c~+ 3 K can be expected due to the powder pressing, which is of the order of magnitude of the value found experimentally (Fig. 4).…”
Section: Comparison With Theoriessupporting
confidence: 72%
“…Effect of uniaxial pressure on the phase transition temperature of TGS was reported by Imai [13] with a rate of -6.7 K/kbar, -9.1 K/kbar and 19.0 K/kbar for a * -, b-and c-axis, respectively. Koralewski et al [14] was reported in the case of TGSe with a rate of -15.9 K/kbar, -8.7 K/kbar and 28.3 K/kbar for a * -, b-and c-axis, respectively.…”
Section: /[346]mentioning
confidence: 95%
“…A hydrostatic pressure applied to the crystal does not change this ratio (Gesi et ul., 1995), which could speak against the tricritical point behaviour. It is nevertheless possible that an uniaxial stress along the crystallographic direction [OOl] would be more efficient Downloaded by [University of Western Ontario] at 20:17 17 November 2014 in displacing the system from the tricritical point in analogy with TGSe crystal (Koralewski et al, 1997). It is worth noting that so-called "logarithmic corrections" to the critical behaviour also predict the ratio -4 for the inverse susceptibilities even in the case of an usual critical point (see for example Binder et al, 1976).…”
Section: Discussionmentioning
confidence: 99%